WDR11‐mediated Hedgehog signalling defects underlie a new ciliopathy related to Kallmann syndrome. (20th December 2017) - Kim, Yeon‐Joo; Osborn, Daniel PS; Lee, Ji‐Young; Araki, Masatake; Araki, Kimi; Mohun, Timothy; Känsäkoski, Johanna; Brandstack, Nina; Kim, Hyun‐Taek; Miralles, Francesc; Kim, Cheol‐Hee; Brown, Nigel A; et al.
Abstract: WDR11 has been implicated in congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome (KS), human developmental genetic disorders defined by delayed puberty and infertility. However, WDR11's role in development is poorly understood. Here, we report that WDR11 modulates the Hedgehog (Hh) signalling pathway and is essential for ciliogenesis. Disruption of WDR11 expression in mouse and zebrafish results in phenotypic characteristics associated with defective Hh signalling, accompanied by dysgenesis of ciliated tissues. Wdr11 ‐null mice also exhibit early‐onset obesity. We find that WDR11 shuttles from the cilium to the nucleus in response to Hh signalling. WDR11 regulates the proteolytic processing of GLI3 and cooperates with the transcription factor EMX1 in the induction of downstream Hh pathway gene expression and gonadotrophin‐releasing hormone production. The CHH/KS‐associated human mutations result in loss of function of WDR11. Treatment with the Hh agonist purmorphamine partially rescues the WDR11 haploinsufficiency phenotypes. Our study reveals a novel class of ciliopathy caused by WDR11 mutations and suggests that CHH/KS may be a part of the human ciliopathy spectrum. Synopsis: WDR11, the causative gene for congenital hypogonadotrophic hypogonadism and Kallmann syndrome, promotes Hedgehog singaling and ciliogenesis, linking these diseases to the human ciliopathy spectrum. WDR11 functions as a novel element of the Hedgehog (Hh) signal pathway, which regulates fundamental aspects of mammalian development. WDR11 shuttles between the nucleus and cytoplasm in response to Hh‐signaling. WDR11 is required for the processing of GLI3 protein, forms a tertiary complex with EMX1 and GLI3 and regulates the expression of novel target genes EMX1/2 and GNRH1. WDR11 is a cilia‐associated protein suggesting that CHH/KS with WDR11 mutations are ciliopathy disorders. Abstract : WDR11, the causative gene for congenital hypogonadotrophic hypogonadism and Kallmann syndrome, promotes Hedgehog singaling and ciliogenesis, linking these diseases to the human ciliopathy spectrum.